Tricuspid regurgitation progression and regression in pulmonary arterial hypertension: implications for right ventricular and tricuspid valve apparatus geometry and patients outcome. (11th February 2016) - Medvedofsky, Diego; Aronson, Doron; Gomberg-Maitland, Mardi; Thomeas, Vasiliki; Rich, Stuart; Spencer, Kirk; Mor-Avi, Victor; Addetia, Karima; Lang, Roberto M.; Shiran, Avinoam
Abstract : Aims The aim of this study was to determine the mechanism of tricuspid regurgitation (TR) progression in pulmonary arterial hypertension (PAH) and its effect on survival. Methods and results We studied 88 patients with PAH and functional TR (mean pulmonary artery pressure 49 ± 14 mmHg; 43% idiopathic PAH) who had serial echocardiograms. TR progression ( n = 35) was defined as ≤mild TR on Echo 1 and ≥moderate TR on Echo 2. TR regression ( n = 17) was defined as ≥moderate TR on Echo 1 and ≤mild TR on Echo 2. Stable TR ( n = 36) was defined as ≤mild TR on both echoes. TR progression was associated with an increase in pulmonary artery systolic pressure (PASP, 62 ± 22–92 ± 23 mmHg, P < 0.0001), right ventricular (RV) enlargement, mainly at mid-ventricular level, increased RV sphericity (6.1 ± 1.7–6.9 ± 1.8, P = 0.004), tricuspid annular (TA) dilatation (4.0 ± 0.7–4.6 ± 0.7 cm, P < 0.0001), and increased tricuspid valve (TV) tenting area (2.0 ± 0.7–2.5 ± 1.0 cm 2, P = 0.0003). TR regression was associated with a reduction in PASP (84 ± 15–55 ± 18 mmHg, P < 0.0001), reverse RV remodelling with a reduction in RV sphericity (6.3 ± 1.4–5.5 ± 1.0, P = 0.02), and a reduction in TA size (4.1 ± 0.7–3.6 ± 0.7 cm, P = 0.02) and TV tenting (2.1 ± 0.7–1.3 ± 0.5 cm 2, P = 0.0002). TR progression was associated with all-cause mortality (log-rank P = 0.0007). Conclusion In PAH, TR progression was associated with worsening pulmonary hypertension and adverse RV and TV apparatus remodelling. TR progression is associated with poor outcome in PAH.